DIARY NOTES OF VOLODYMYR MALYK Volodymyr Malyk. Dark blue book: Diary (messages on your own). 1958- 1998 / Managers O.V.Sichenko, N.O.Sichenko. – Poltava: LTD “ASMI”, 2010. – 308 s., il. - Baran, Ye. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The author of review analyses to the diary note by Volodymyr Malyk (1921-1998), that are given out as a separate book recently in Poltava.